Character Education in Educational Policies and Cultural Integration: Indonesia and Turkiye - Genta Qory Aisya (Yayasan Al-Afif, 2025)
This study examines character education frameworks within Indonesia’s Merdeka Curriculum and Turkiye’s Türkiye Yüzyılı Maarif Modeli (TYMM), analyzing how cultural values are embedded and their role in promoting cultural integration. Through a comparative analysis, the study explores the similarities and differences between Indonesia’s Pancasila Student Profile, which is implemented through the Pancasila Student Profile Strengthening Project (P5) project-based learning program that emphasizes unity in diversity, and Turkiye’s Yetkin ve Erdemli (Competent and Virtuous) Student Profile, which is conceptualized through a comprehensive framework of Erdem-Değer-Eylem (Virtue-Value-Action) that prioritizes national identity and spiritual values.